Distribution of deuterons in the three-body break-up reaction in D + D collisions - Beliuskina, O.O.; Grantsev, V.I.; Kisurin, K.K.; Omelchuk, S.E.; Roznyuk, Yu.S.; Rudenko, B.A.; Semenov, V.S.; Slusarenko, L.I.; Struzhko, B.G. (Вопросы атомной науки и техники, 2013)
The energy distributions of deuterons from the reaction D + D → p + n +d were measured in the angular range of 15° ≤ θc.m. ≤ 35° at ED = 36.9 MeV . The experiment was carried out on the cyclotron U-240 of INR NAS of Ukraine. Microscopic diffraction model was used for analysis of experimental data taking into account the interaction of nucleons in the final state. Two types of three-body reactions were considered: 1) break-up of the target nucleus with formation of scattered deuterons d' and 2) break-up incident deuteron with formation of recoil deuterons d¯. Experimental energy distributions of deuterons are described satisfactorily both by shape and by absolute value, taking into account total contribution of cross sections of deuterons d' and d¯.